Samsang gjennom livsløpet - Vesterlid Strøm, Regine; Eiksund, Øyvind Johan; Haugland Balsnes, Anne (MusPed:Research, 2022)
This anthology deals with co-singing (Norwegian: samsang) in different life stages and various settings in a Scandinavian context. Co-singing forms an essential part of our shared cultural heritage. Co-singing involves all forms of singing-activities in which people coexist, and characterizes in various ways human companionship throughout the course of life, from cradle to grave. From a critical analytical perspective, the research in this anthology sheds light on several themes related to the importance and value of co-singing practice in terms of sensemaking and experiencing coherence in life. This involves musical, physical, psychological, emotional, cognitive, ethical, cultural, and social factors. The research project examines for instance the position of singing activities in Norwegian kindergartens and schools, co-singing and health-related topics, co-singing from a gender perspective, co-singing from a multicultural perspective, co-singing activities in light of motivation and coping, and also low-threshold, flexible daily life singing activities for persons with dementia and their relatives. Choir singing in various life stages, from childhood to age of retirement, are also explored in several chapters. With its broadly arranged and pluralistic approach, this anthology provides a multi-faceted contribution to the development of knowledge in the research field of music associated with the power and legitimacy of co-singing at the individual, group, and societal levels. The contributing authors have their practical and scientific experience from higher music education within the fields of music pedagogy, music performance, music therapy, music and health, and also from other types of cultural and musical practices.